Penerapan Metode Pembelajaran Jigsaw Berbantuan Video Interaktif untuk Meningkatkan Hasil Belajar Siswa Kelas XI di SMAN 1 Kerinci Kanan - Ardilah, Ardilah; Rahayu, Indah Ayu Puji; Ertiana, Ira; Aisah, Siti (Medan Resource Center, 2023)
This research aimed to investigate the effectiveness of the jigsaw learning method assisted by interactive videos in enhancing the learning outcomes of class XI-IPA students at SMAN 1 Kerinci Kanan, specifically focusing on the human digestive system subject. Utilizing a single-cycle PTK (classroom action research) involving planning, implementation, and reflection stages within two meetings, the study engaged 16 students, comprising 7 females and 9 males. Data collection involved interactive learning activities, group discussions, presentations, and reflections on completed Student Worksheets (LKPD). The outcomes revealed a notable improvement in students' learning achievements, indicating the success of the jigsaw method assisted by video learning media in augmenting the knowledge of the students through collaborative activities, presentations, and discussions. The findings underscore the potential of integrating interactive videos with the jigsaw method as an effective approach for enhancing comprehension and engagement in learning the human digestive system among high school students.